2010
DOI: 10.1097/gme.0b013e3181dbdc30
|View full text |Cite
|
Sign up to set email alerts
|

Serum lipid profile changes during the menopausal transition in Chinese women

Abstract: Our data suggest that the menopausal transition instead of menopause per se is associated with serum lipid profile in community-based women in China. Late perimenopause status is significantly associated with accelerated increase in TC, TG, and TC/HDL-C. HDL-C seemed to have no relationship with menopause status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
25
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 31 publications
6
25
1
Order By: Relevance
“…LDL-C is a major cause of CHD, as well as the primary target of lipid-lowering therapy 26 . BMI has been found to be related to TC 8,9 and LDL-C 8 concentrations in BCS, similar to findings in non-BCS 6 . A study of 104 Brazilian postmenopausal BCS found that the rates of high TC and high LDL-C were 56.7 and 83.4%, respectively 31 .…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…LDL-C is a major cause of CHD, as well as the primary target of lipid-lowering therapy 26 . BMI has been found to be related to TC 8,9 and LDL-C 8 concentrations in BCS, similar to findings in non-BCS 6 . A study of 104 Brazilian postmenopausal BCS found that the rates of high TC and high LDL-C were 56.7 and 83.4%, respectively 31 .…”
Section: Discussionsupporting
confidence: 66%
“…A study of 104 Brazilian postmenopausal BCS found that the rates of high TC and high LDL-C were 56.7 and 83.4%, respectively 31 . Moreover, a prospective study of non-BCS found that the menopause transition was associated with significant increases in TC and TG concentrations 6 . The Study of Women's Health Across the Nation (SWAN) found that TC, LDL-C and TG levels peaked during late perimenopause and early postmenopause 5 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a Chinese study reported different results showing that only late perimenopausal status was associated with lipid abnormalities [6]. In that study, women in late perimenopause (2-12 months of amenorrhea once during a year) had significantly higher levels of TC, TG, and TC/HDL-C ratios compared with women in pre-menopause independent of age, BMI, and other confounding factors, while LDL-C levels were not significantly elevated; however, there were no significant changes in HDL-C with menopausal stages [6]. There have been inconsistent results with regard to TG changes during menopause.…”
Section: Discussionmentioning
confidence: 91%
“…Epidemiological studies found greater levels of total cholesterol (TC), low density lipoproteincholesterol (LDL-C), triglycerides (TG), and apolipoprotein B (Apo B) in post-menopausal compared to pre-menopausal women; inconsistent results were found for HDL cholesterol (HDL-C) [3,4]. Other studies reported that the perimenopausal period was associated with elevated total cholesterol, LDL-C, TG, and TC/HDL-C ratio [5,6] and that the greatest increase in HDL-C level was observed in late perimenopause and early post-menopause [5].…”
Section: Introductionmentioning
confidence: 95%